73.6k views
4 votes
Graph function g
f(x)=(x-1)^2-5
g(x)=f(x+2)

Graph function g f(x)=(x-1)^2-5 g(x)=f(x+2)-example-1
Graph function g f(x)=(x-1)^2-5 g(x)=f(x+2)-example-1
Graph function g f(x)=(x-1)^2-5 g(x)=f(x+2)-example-2
Graph function g f(x)=(x-1)^2-5 g(x)=f(x+2)-example-3
Graph function g f(x)=(x-1)^2-5 g(x)=f(x+2)-example-4

1 Answer

1 vote

9514 1404 393

Answer:

C (see below)

Explanation:

The function f(x) is written in vertex form:

f(x) = a(x -h)^2 +k . . . . . scale factor 'a', vertex (h, k)

The vertex of function f(x) is (1, -5).

The function g(x) = f(x +2) represents a shift left by 2 units. When the vertex of f(x) is shifted left 2 units, it becomes (1-2, -5) = (-1, -5).

The graph with the vertex in this location is the third problem attachment, shown below.

Graph function g f(x)=(x-1)^2-5 g(x)=f(x+2)-example-1
User Sandeep Kumar P K
by
5.8k points